Cover Feature: Highly Selective Catalytic Dechlorination of Dichloromethane to Chloromethane over Al−Ti Mixed Oxide Catalysts (ChemCatChem 20/2020). Issue 20 (21st September 2020) - Yoon, Wongeun; Lee, Seungjun; Noh, Yuseong; Park, Seongmin; Kim, Youngmin; Ju Kim, Hyung; Chae, Ho‐Jeong; Bae Kim, Won
Abstract : The Cover Feature shows the selective dechlorination of dichloromethane (CH2 Cl2 ) to chloromethane (CH3 Cl) in the presence of water with the help of mixed oxide catalyst to achieve high overall production yield of chloromethane, which is an important value‐added intermediate in the chemical industry. In their Full Paper, W. Yoon et al. investigated a series of Al‐Ti mixed oxides with different Al/Ti ratios as active catalysts for the selective dechlorination of dichloromethane and found that the strong and abundant Lewis acid sites generated by Al‐O‐Ti bonds in the optimum Al‐Ti mixed oxide are responsible for the much enhanced catalytic performance in the selective dechlorination reaction. Their results suggest that mixed oxide system can be a good candidate for the effective catalytic dechlorination of polychlorinated products. More information can be found in the Full Paper by W. Yoon et al.